Concomitant Embolization and Microsurgical Resection of a Giant, Hypervascular Skull Base Meningioma: 2-Dimensional Operative Video. Issue 2 (30th April 2021) - Mooney, Michael A; Ibn Essayed, Walid; Aziz-Sultan, Mohammad Ali; Al-Mefty, Ossama
Abstract: Some skull base tumors can be extremely hypervascular, incorporating multiple vascular territories and demonstrating arteriovenous shunting. Devascularization is a critical step undertaken early in meningioma surgery, necessary before the debulking that is required in skull base tumors. While devascularization can often be achieved with appropriate approach selection, bony drilling, and microsurgical cautery, preoperative embolization of meningiomas has an invaluable role in selected cases. 1, 2 Embolization, however, does have added risk, magnified in large tumors by the potential infarction with subsequent edema that can potentially lead to acute deterioration and neurosurgical emergency. Hence, to achieve devascularization of an extremely vascular tumor, embolization and surgical resection should be performed concomitantly, as one operation, in which embolization might be the first stage, or might be performed after the craniotomy flap is raised, if necessary. 3 Naturally, this requires the multifaceted neurosurgical expertise of embolization and microsurgical resection, and the facility to perform such. We present a case of a giant, hypervascular, radiation-induced, skull base meningioma with internal and external carotid artery supply in a young patient with deteriorating vision in his only eye. Selective embolization of the internal maxillary, middle meningeal, and middle cerebral artery blood supplies was performed. Microsurgical interruption of the ethmoidal artery blood supply was then performed. This hybrid approach safely and effectively devascularized the tumor and allowed for a complete resection of this high-risk tumor 4 while minimizing risk to the ophthalmic artery and optic nerve. The patient was consented for surgery.